Design of a rehabilitation device for thrombosis: a mathematical modelling activity in the training of engineers - Siero González, Luis Ramón; Echavarría Cepeda, Lenin Augusto; Romo Vázquez, Avenilde; Navarro Torres, José (Avances de investigación en educación matemática = Advances of research in mathematics education, 2022)
The research reported here is framed in the problem of proposing and analysing conducive mathematics teaching for future engineers. It considers that establishing relationships between mathematics and engineering courses is the first step towards training mathematically-competent engineers. In the frame of the Anthropological Theory of the Didactic, one approach to this problem consists of analysing mathematical modelling activities in engineering and transposing it to school. This work presents how a group of engineering students developed a rehabilitation device for thrombosis, relating different types of knowledge: mathematical, engineering, and practice come from different courses and the investigations made for this project.